Analisis Kemampuan Pemecahan Masalah Matematis Siswa Ditinjau dari Kecemasan Matematis dalam Menyelesaikan Soal Cerita SPLTV - Ayunda Nova Millania; Nur Fauziyah (DIDAKTIKA, 2024)
Mathematical anxiety is one condition that can hinder the learning process. This research aims to describe students' abilities in solving mathematical problems as viewed from low, medium, and high levels of mathematical anxiety. The method used in this research is qualitative descriptive. The subjects used are 3 students from class X of Muhammadiyah 1 High School in Gresik, selected based on low, medium, and high levels of mathematical anxiety. The data collection techniques used are a mathematical anxiety questionnaire, problem-solving ability tests with story problems on linear equations, and interviews. The data analysis techniques in this study are data reduction, data presentation, and conclusion. The results of this study indicate that students with low mathematical anxiety are able to meet the indicators of mathematical problem-solving according to Polya's steps, which are understanding the problem, planning the solution, solving the problem, and checking back. Students with moderate mathematical anxiety are only able to meet two indicators, namely understanding the problem and planning the solution. Then, students with high mathematical anxiety are unable to meet all the indicators of mathematical problem-solving skills.